Central Asian States: Difficulties on the Path of Rapprochement - G. Ch. Akunova (Проблемы постсоветского пространства)
After the collapse of the Soviet Union, the new independent states of Central Asia had faced serious problems, such as the lack of experience in building state system, border demarcation, severe economic situation, threat of interethnic conflicts. However, that period was appropriate for integration initiatives in Central Asia. The economies of the post-Soviet republics in the region had been formed by the common Soviet system, the states depended from each other. In addition, the geopolitical situation in the region was favorable for rapprochement; Russia, China, the United States were not actively involved in regional processes. In the period from 1994 to 2005, the Central Asian republics initiated several integration projects, such as the Common economic space (Kazakhstan, Uzbekistan, and Kyrgyzstan), the Central Asian Economic Community (Kazakhstan, Uzbekistan, Kyrgyzstan and Tajikistan), the Central Asian Cooperation Organization (all republics of Central Asia, except Turkmenistan). It should be noted that the integration process in the region implied all republics of Central Asia, except Turkmenistan, which had been ignoring any initiatives of neighbor countries. These structures did not achieve their goal, such as the creation of a free trade zone as well as customs, currency and payment unions. After a prolonged period of integration initiatives, there were no real close relationships between the countries. The states still prefer to build their relations in a bilateral format. The article considers the reasons that prevent the Central Asian states from effectively pursuing a multilateral format of cooperation in the region. The main reasons that determine the unpreparedness of Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan for cooperation in a multilateral format are identified. Attention has been paid to such factors as the collision of interests of outside players, leadership issues between Kazakhstan and Uzbekistan, water distribution policy and cross-border cooperation. The steps that Central Asian countries need to take to establish effective multilateral cooperation in the region are analyzed.